Determinants of Malaria Vaccine Acceptance: A Systematic Review and Meta‐Analysis of Awareness, Acceptance, Hesitancy, and Willingness to Pay - Ganesh Bushi; Mahalaqua Nazli Khatib; Renuka Jyothi. S; Irwanjot Kaur; Abhishek Sharma; Suhaib Iqbal; M. Ravi Kumar; Ashish Singh Chauhan; Teena Vishwakarma; Praveen Malik; Quazi Syed Zahiruddin; Mahendra Pratap Singh; et al. (Immunity, Inflammation and Disease)
ABSTRACT Background Malaria is a life‐threatening disease caused by Plasmodium parasites, transmitted through the bites of infected female Anopheles mosquitoes. It remains a major global health issue, with 263 million cases and 597,000 deaths in 2023, primarily affecting young children and pregnant women. This review evaluates awareness, acceptance, hesitancy, and willingness to pay (WTP) for the RTS,S/AS01 malaria vaccine, along with the key factors influencing these outcomes. Methods A comprehensive literature search was conducted in Web of Science, PubMed, and Embase, covering publications up to 18 June 2024. Observational studies assessing awareness, acceptance, hesitancy, and WTP for the malaria vaccine in endemic regions were included. Two independent reviewers screened the studies. Data extraction was performed using Nested Knowledge software and analyzed with R v.4.4. Pooled prevalences were estimated using random‐effects models, and heterogeneity was assessed with the I² statistic. Results Eighteen studies with 21,975 participants provided insights into malaria vaccine dynamics: 32% awareness (95% CI, 18%–50%), 83% acceptance (95% CI, 75%–89%), 14% hesitancy (95% CI, 7%–26%), and 58% WTP (95% CI, 34%–79%). Key determinants of acceptance included age, where younger adults (18–24 years) showed lower acceptance (OR = 0.64, 95% CI, 0.35–0.93). Employment, particularly farmers, had higher acceptance rates (OR = 3.20, 95% CI, 1.00–7.40). Lower socioeconomic status and larger family sizes were associated with decreased acceptance (OR = 0.18, 95% CI, 0.02–0.38). Conclusion This review revealed an 83% acceptance rate for the malaria vaccine, with variability in awareness (32%), hesitancy (14%), and willingness to pay (58%). Age, employment, and socioeconomic status were significant determinants of acceptance. However, due to potential publication bias and high heterogeneity, these findings should be cautiously interpreted. The results highlight the necessity for targeted interventions to enhance vaccine acceptance. Further research is required to elucidate factors that influence vaccine acceptance.